Comparison between the United States and Mexico of Main food sources, 1961–2010 - Mendoza Guerrero, Juan Manuel; Restrepo Betancur, Fernando; Bruno Fiscal, Carlos (Agricultura, Sociedad y Desarrollo, 2020)
The availability of foods allows the population to have caloric and energetic sources of plant and animal origin that are ideal for their welfare. Therefore, it is of vital interest to know the statistics associated with it, in order to have planning according to the requirements of the population. The objective of this article is to compare both the availability of meat (pork, beef, fish and poultry), egg, milk, wheat, vegetables, legumes, fruits and beans, as well as the sources of energy, protein and fat in the period of 1961-2010 between the United States and Mexico. For this purpose, multivariate variance analysis (MANOVA) with orthogonal canonic contrast, principal components analysis and unidimensional exploratory descriptive analysis were performed, where information from the FAOSTAT database was taken into account. The main conclusion is that there is asymmetry in the availability of foods, ever decreasing, in favor of the United States, in addition to a difference in the types of foods available since while the United States points to a diet based on poultry and dairy, Mexico bases its diet on pork and dairy.